2021
DOI: 10.1007/s11240-021-02206-z
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cytokinins on shoot proliferation, biochemical changes and genetic stability of Rhododendron ‘Kazimierz Odnowiciel’ in the in vitro cultures

Abstract: Shoot proliferation is a very important micropropagation phase, decisive for economic efficiency of this method for a given taxon. To obtain a high multiplication ratio and a good quality of microshoots a detailed propagation protocol must be developed for particular species or even cultivars. Rhododendron ‘Kazimierz Odnowiciel’ is a relatively new cultivar distinguished by large, beautiful flowers and high frost resistance so there is a need to develop an efficient method of its propagation to satisfy a growi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 54 publications
2
17
0
1
Order By: Relevance
“…Wei et al (2018) , for example, grew R. fortunei seedlings in vitro and developed the most appropriate conditions for micropropagation [7]. Nowakowska et al (2022) cultured Rhododendron 'Kazimierz Odnowiciel' in vitro and demonstrated the effect of cytokinins on shoot proliferation and genetic stability of plants [8]. However, the in vitro propagation of many endangered Rhododendron species, e.g.…”
Section: Of 19mentioning
confidence: 99%
See 2 more Smart Citations
“…Wei et al (2018) , for example, grew R. fortunei seedlings in vitro and developed the most appropriate conditions for micropropagation [7]. Nowakowska et al (2022) cultured Rhododendron 'Kazimierz Odnowiciel' in vitro and demonstrated the effect of cytokinins on shoot proliferation and genetic stability of plants [8]. However, the in vitro propagation of many endangered Rhododendron species, e.g.…”
Section: Of 19mentioning
confidence: 99%
“…The IRAP markers showed a high polymorphism in Rhododendron plants, as high as 96.7%, which are close to those of 94% of polymorphisms in Bletilla striata [25], and 98% of polymorphisms in Phyllostachys species [26] as calculated by IRAPs, respectively. Previously, ISSRs were demonstrated to be polymorphic for genetic variation detection [8], currently, IRAP marker was justified to be more effective in polymorphism assessment for rhododendrons. Likewise, EMR is the number of markers generated per primer assay [22], and the EMR value for IRAPs (14.55) was greater than that for ISSRs (12.21).…”
Section: Iraps and Its Effectiveness In Genetic Divergence Detection ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Konsentrasi BAP yang terlalu tinggi menyebabkan ketidakseimbangan metabolisme dalam jaringan yang bisa jadi memperlambat proliferasi tunas. Nowakowska et al (2022), peningkatan sitokinin pada regenerasi tunas meningkatkan kandungan hidrogen peroksida yang menjadi berbahaya karena dapat merusak elemen sel struktural akibat oksidasi dan degradasi yang memicu kematian sel sehingga memperlambat regenerasi tunas.…”
Section: Hasil Dan Pembahasanunclassified
“…Shoot multiplication is the most crucial step in the development of an efficient micropropagation protocol that directly affects the success of the given protocol ( Pati et al., 2006 ; Nowakowska et al., 2022 ) ( Figures 2 c, 2d). Various factors that greatly influence the shoot multiplication in bananas are highlighted in this section.…”
Section: Micropropagation Of Bananamentioning
confidence: 99%